Protein clustering in chemically stressed HeLa cells studied by infrared nanospectroscopy. Issue 40 (29th September 2016) - Giliberti, V.; Baldassarre, L.; Rosa, A.; de Turris, V.; Ortolani, M.; Calvani, P.; Nucara, A.
Abstract : Photo-Thermal Induced Resonance (PTIR) nanospectroscopy, tuned towards amide-I absorption, was used to study the distribution of proteic material in 34 different HeLa cells, of which 18 were chemically stressed by oxidative stress with Na3 AsO3 . Abstract : Photo-Thermal Induced Resonance (PTIR) nanospectroscopy, tuned towards amide-I absorption, was used to study the distribution of proteic material in 34 different HeLa cells, of which 18 were chemically stressed by oxidative stress with Na3 AsO3 . The cell nucleus was found to provide a weaker amide-I signal than the surrounding cytoplasm, while the strongest PTIR signal comes from the perinuclear region. AFM topography shows that the cells exposed to oxidative stress undergo a volume reduction with respect to the control cells, through an accumulation of the proteic material around and above the nucleus. This is confirmed by the PTIR maps of the cytoplasm, where the pixels providing a high amide-I signal were identified with a space resolution of ∼300 × 300 nm. By analyzing their distribution with two different statistical procedures we found that the probability to find protein clusters smaller than 0.6 μm in the cytoplasm of stressed HeLa cells is higher by 35% than in the control cells. These results indicate that it is possible to study proteic clustering within single cells by label-free optical nanospectroscopy.